Pertumbuhan dan Uji Gula Reduksi 5 Isolat Jamur Asal Batang Kelapa Sawit ke Potongan Batang Kelapa Sawit - Poltak Mangatur Tua Sirait; Tengku Sabrina; Asmarlaili Sahar Hanafiah (Jurnal Pertanian Tropik, 2018)
Fungi is a microorganism that has been widely used to accelerate the rate of decomposition of organic matter. This research was conducted in the soil biology laboratory of the Faculty of Agriculture, University of Sumatera Utara. This study was aimed to examine the potential of fungi isolates derived from palm oil trunks. This research begins by isolating the fungi contained in the cutting of oil palm trunk from the plant rejuvenation. The isolate is purified to obtain a pure culture. Selected isolates were identified by DNA sequencing using PCS 28s ITS and the results were identified as Rhizopus arrhizus Strain ATCC 111450 (A), Rhizopus microspores var rhozopodiformis Strain IFM 46417 (B) Syncephalastrum racemosum isolate VPCI 1857/11) (C), Trichoderma asperellum Strain ATCC 52438 (D), and Trichoderma asperellum Strain G (E). All isolates were applied to sterilized palm oil trunks. The results of this study were Rhizopus microspores var rhozopodiformis Strain IFM 46417 capable of growing well in pH 4, 6, and 8, Trichoderma asperellum Strain G (E) had the fastest growth rate of 64.58 mm / day. Test of cellulase enzyme production by using a method of Fehling A and B aiming at the fungus Trichoderma asperellum Strain G (E) produces the highest cellulase enzyme.